Predictive modelling for the growth of Bacillus cereus in Reconstituted Infant Gormula and culture medium at population and single cell levels - Silva, Nathália Buss da (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2019.